Rumah Kreatif (RK) Baubau's Successful Learning Methods For Speaking Performance - Hasrida Ardin; Nurhayati Nurhayati; Afianti Afianti (Hasanuddin University, 2026)
The purpose of this study was to outline the successful speaking performance learning techniques used by the Rumah Kreatif (RK) Baubau. The problem statement,